123 Natural killer cells engineered with an inducible, responsive genetic construct targeting TIGIT and CD73 to relieve immunosuppression within the GBM microenvironment. (10th December 2020) - Lupo, Kyle; Matosevic, Sandro
Abstract : Background: Solid tumors such as GBM are particularly difficult to treat, being largely resistant to traditional treatments, fueling interest in alternative treatment approaches, including cell-based immunotherapy. Natural killer (NK) cells have emerged as promising effectors to target GBM through genetic modifications and ex vivo manipulation. However, immunosuppressive conditions within the tumor microenvironment (TME) further complicate NK cell-based treatments. Specifically, within the TME tumor cells release of high levels of ATP extracellularly. While intracellular ATP is necessary for cell metabolism, extracellular ATP is converted into adenosine (ADO) by ectonucleotidases CD39 and CD73, both overexpressed on GBM. 1 Extracellular ADO induces immunometabolic suppression of NK cells through binding with A2A adenosine receptors (A2ARs) on NK cells, suppressing cytokine secretion, proliferation, and other functional activities. 2–4 Adding to the suppression of NK cells is the interaction between CD155, expressed highly on GBM and other solid tumors, and T cell immunoreceptor with Ig and ITIM domains (TIGIT) expressed on NK cells. This interaction signals inhibition of NK cell cytolytic function, allowing for cancer cell immune-evasion. 5 6 Methods: To restore impaired NK cell anti-tumor activity, we have engineered NK cells to concomitantly target CD155 and CD73-induced immunosuppression on GBM using a tumor-responsive genetic construct. The construct is capable of blocking the immunosuppressive CD155/TIGIT interaction, and, upon binding, release a CD73-blocking scFv to inhibit the accumulation of extracellular ADO and mitigate immunosuppression of NK cells. Such localized response enhances specificity and reduces off-target effects of NK-based targeting. Results: Primary NK cells were successfully electroporated to express our synthetic TIGIT-synNotch construct, as evidenced by increased expression levels of TIGIT (% and MFI) (figure 1 ). To evaluate the functionality of engineered NK cells against GBM targets, we tested the cytotoxicity of our engineered NK cells against a primary, patient-derived GBM cell line, GBM43. Overall, cytolytic function of engineered NK cells against GBM was significantly higher than that of non-engineered NK cells, with or without CD73 (10 ug/mL) and TIGIT (50 ug/mL) antibodies, for E:T ratios of 5:1 and 10:1 (figure 2 ), demonstrating the functional efficacy of our genetic construct. Further, engineered NK cells (T-PNK) expressed significantly higher levels of CD107a in response to GBM43 stimulation than non-engineered PNK at E:T ratios 2.5:1 and 10:1 (figure 3 ). Conclusions: Overall, we have shown that co-targeting CD155 and CD73 in a localized, responsive manner can dampen immunosuppression and significantly enhance the killing potential of engineered NK cells against aggressive patient-derived GBM tumors. References: Chambers AM, et al. Adenosinergic Signaling Alters Natural Killer Cell Functional Responses. Front. Immunol 2018;9 :2533. Chambers AM, Lupo KB & Matosevic S. Tumor microenvironment-induced immunometabolic reprogramming of natural killer cells. Front Immunol 2018;9 :2517. Chambers AM, et al. Adenosinergic signaling alters natural killer cell functional responses. Front. Immunol 2018;9 :2533. Wang, J., Lupo, K. B., Chambers, A. M. & Matosevic, S. Purinergic targeting enhances immunotherapy of CD73+ solid tumors with piggyBac-engineered chimeric antigen receptor natural killer cells. J. immunotherapy cancer 2018;6 :136. Zhang B, et al. Immunoreceptor TIGIT inhibits the cytotoxicity of human cytokine-induced killer cells by interacting with CD155. Cancer Immunol Immunother 2016;65 :305–314. Lupo KB & Matosevic S. CD155 immunoregulation as a target for natural killer cell immunotherapy in glioblastoma. J Hematol Oncol 2020;13 :76.